The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.5152/akd.2010.086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeic acid phenethyl ester on isoproterenol-induced myocardial infarction in rats

Abstract: ÖZETAmaç: Kafeik asit fenetil ester (CAPE) güçlü antiinflamatuvar, anti-tümör ve antioksidan özelliklere sahip doğal bir üründür ve iskemireperfüzyonun indüklediği inflamasyonu ve lipid peroksidasyonu azaltır. Bu çalışmanın amacı isoproterenol (ISO) indüklü miyokardiyal infarktüs üzerine CAPE tedavisinin etkilerini incelemektir. Yöntemler: Bu çalışmada rasgele deneysel kontrollü araştırma dizaynı seçildi. Sıçanlar dört gruba ayrıldı: Kontrol, CAPE, ISO, ISO+CAPE. CAPE (10 μmol kg/gün i.p.) ve ISO (150 mg /kg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…In the previous studies reported that L-NNA decreases the activities of antioxidant enzymes and enhances lipid peroxidation (29). In accordance with previous studies, it was observed that 150 mg/kg dose of ISO induced a myocardial damage and significantly altered biochemical parameters and antioxidant enzyme activities in the present study (13). In the present study ISO administration caused myocardial damage which was reflected by a significant increase in serum AST and LDH levels.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the previous studies reported that L-NNA decreases the activities of antioxidant enzymes and enhances lipid peroxidation (29). In accordance with previous studies, it was observed that 150 mg/kg dose of ISO induced a myocardial damage and significantly altered biochemical parameters and antioxidant enzyme activities in the present study (13). In the present study ISO administration caused myocardial damage which was reflected by a significant increase in serum AST and LDH levels.…”
Section: Discussionsupporting
confidence: 81%
“…Myeloperoxidase (MPO) is a neutrophil and monocyte enzyme that amplifies the reactivity of hydrogen peroxide (33). We did not measure MPO activity, but we previously showed that CAPE decreases the rised MPO activity in heart (13). MPO and its oxidation products can play a key role for the enzyme in promoting of lipid peroxidation and other oxidative modifications in acute myocardial infarction (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28) From this finding, CAPE may attenuate the development of obesity in rodents. Furthermore, the protective effect of CAPE on the development of the cardiovascular system 29,30) and myocardial injury 31) in rodents was documented. This arterial dysfunction is regulated by the expression of adipokines such as, leptin, resistin and TNF-alpha.…”
Section: Discussionmentioning
confidence: 99%
“…SEA was chosen over SEB since SEA has the ability to bind both MHC IIα and MHC IIβ chains resulting in the upregulation of costimulatory molecules on the APC along with the production of proinflammatory cytokines. This results in more robust T cell stimulation compared to SEB, which better mimics the human situation [24, 25]. …”
Section: Introductionmentioning
confidence: 99%